Cell Saver Use in Acetabular Surgery: Does Approach Matter?. Issue 8 (August 2015) - Firoozabadi, Reza; Swenson, Alan; Kleweno, Conor; Routt, Milton C.
Abstract : Objective: To determine if intraoperative autologous transfusion using a Cell Saver (CS) was routinely indicated for open reduction internal fixation (ORIF) of acetabular fractures, and if so, was there a difference between differing surgical approaches. Design: Retrospective single-center cohort study. Setting: University Level 1 trauma center. Patients/Participants: One hundred forty-five consecutive acetabular fractures using intraoperative autologous transfusion, either treated with an anterior ilioinguinal or a posterior-based Kocher–Langenbeck approach, were compared. Intervention: Use of CS in ORIF acetabular cases. Main Outcome Measurements: CS utilization and CS blood return for acetabular ORIF. Mean intraoperative blood loss between the 2 approaches. Results: CS blood was returned in 29 of the 145 total cases [23/65 anterior (ilioinguinal approach) and 6/80 posterior approach (Kocher–Langenbeck)]. Mean intraoperative blood loss was 786 mL for the anterior approach and 485 mL for the posterior approach. Subgroup analysis identified anterior approach as the only risk factor for elevated blood loss and CS blood return. Conclusions: CS is not indicated for routine use when performing ORIF of the acetabulum. Use of the CS may be warranted with anterior approaches if large amounts of blood loss are anticipated. Level of Evidence: Prognostic Level II. See Instructions for Authors for a complete description of levels of evidence.